A 58‐year‐old lady presented as an emergency with right upper quadrant pain and loss of 5 stones in weight. What does the X‐ray show?. Issue 4 (25th July 2014) - Pannu, Arslan Y.; Mallick, Ismail H.; Peter, Mark B.
Key Clinical Message Renal cell cancers are among the great mimics in surgery as they present with myriad symptoms unrelated to the renal cancer. This patient also interestingly had an incidental finding of porcelain gall bladder.